Evaluating methods for determining interior noise levels used in airport sound insulation programs - Schomer, Paul; Freytag, Jack; Waldeck, Randy, 1978- (ACRP report, 2016)
This report provides guidance for selecting and implementing methods for measuring noise level reduction in dwellings associated with airport noise insulation programs. The research complements the results of ACRP Report 89: Guidelines for Airport Sound Insulation Programs and was undertaken to assess the accuracy and validity of various noise level reduction measurement procedures currently used in airport noise insulation programs. Acoustical field measurements were made at 10 homes near San Diego International Airport and nine homes near Boston Logan International Airport. Seven measurement methods were tested: outdoor ground-level artificial sound source (loudspeaker); outdoor elevated artificial source (loudspeaker); indoor artificial sound source (loudspeaker); aircraft flyover: fixed microphone; aircraft flyover: moving microphone; architectural survey and noise reduction calculations; and acoustic intensity measurements, exterior loudspeaker and interior intensity. The report includes a summary of sound insulation theory and the science behind noise level reduction, and an overview of FAA-sponsored noise insulation programs. The report also provides guidance, including a decision matrix, for selecting an appropriate acoustical testing method. Lastly, the report provides suggested practices for each measurement technique, based on the results of the research.